(untitled) (Repertorio Científico, 2022)
Introduction: The University Council of the UNED of Costa Rica approved, on February, 2019 (Consejo Universitario, 2019), the policy for the implementation of the Universal Design for Learning (UDL); the second principle, to provide multiple means for representation, involves the inclusion of visual materials that contribute to the didactic mediation of the contents; therefore, only the didactic units in the final version have the participation of a graphic designer, not so the rest of the didactic materials of the Written Didactic Material Production Program (PROMADE). Objective: Make a proposal for compliance with the principle of the UDL to provide multiple means of representation in the teaching materials produced by PROMADE, in compliance with CU-2019-096, without this implying an additional cost in terms of computer program licenses for UNED. Method: Analysis, through an exploratory quantitative study, of the use, by academic producers of PROMADE, of Microsoft Visio© software for the elaboration of diagrams and planning and execution of pilot training with academic producers of PROMADE. Results: It was found that, by means of a guide for the use of the program and a minimum investment of 3 hours, academic producers can create their own diagrams in that program, oriented to pedagogical mediation and compliance with principle two of the UDL. Conclusions: Since 2014, UNED officials and students, through their institutional email account, have access to Microsoft Visio©, a program that allows to create easy diagrams. This solution does not imply additional costs in licensing for the institution. Training can be extended to officials from other UNED dependencies through the Distance Education Training Center (CECED for its acronym in Spanish). In addition, this guide could be provided to the student body to comply with principle three providing multiple means of action and expression.